Captioning and Subtitling for d/Deaf and Hard of Hearing Audiences - Zárate, Soledad (UCL Press, 2021)
Captioning and Subtitling for d/Deaf and Hard of Hearing Audiences is a comprehensive guide to the theory and practice of captioning and subtitling, a discipline that has evolved quickly in recent years. This guide is of a practical nature and contains examples and exercises at the end of each chapter. Some of the tasks stimulate reflection on the practice and reception, while others focus on particular captioning and SDH areas, such as paralinguistic features, music and sound effects.The requirements of d/Deaf and hard of hearing audiences are analysed in detail and are accompanied by linguistic and technical considerations. These considerations, though shared with generic subtitling parameters, are discussed specifically with d/Deaf and hard of hearing audiences in mind. The reader will become familiar with the characteristics and needs of d/Deaf and hard of hearing audiences, and the diversity - including cultural and linguistic differences - within this group of people. Based on first-hand experience in the field, the book also provides a step-by-step guide to making live performances accessible to d/Deaf and hard of hearing audiences. As well as exploring all linguistic and technical matters related to the creation of captions, aspects related to the overall set up of the captioned performance are discussed. The guide will be valuable reading to students of audiovisual translation at undergraduate and postgraduate level, to professional subtitlers and captioners, and to any organisation or venue that engages with d/Deaf and hard of hearing people. ; Captioning and Subtitling for d/Deaf and Hard of Hearing Audiences is a comprehensive guide to the theory and practice of captioning and subtitling.